PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SEKTOR REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BEI PERIODE 2016 – 2019 - Sumantri Bratakusuma (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
This study aims to examine Profitability and Leverage Effect on Tax Avoidance. The first research method is determining the of research object, population, sample and data collection techniques. This research used secondary data. This research method used with qualitative analysis are explanation with data description means of translation of minimum, maximum, average, and standard deviation of new variablereserched. Based on the research that has been obtained, it is obtained that Profitability and Leverage have a simultaneous effect on Tax Avoidance in Real Estate and Property from Manufacturing Sector Companies listed on the Indonesia Stock Exchange for the period 2016 - 2019. While partially obtained profitability does not have a significant effect on tax avoidance and leverage has an effect significant to tax avoidance.